Retrievable vena cava filters to protect from venous thromboembolism: do not overuse them, and do not forget to retrieve them! - Konstantinides, Stavros V. (Digestive Medicine Research; Vol 1 (July 2018): Digestive Medicine Research, 2018)
Venous thromboembolism (VTE), clinically presenting as deep vein thrombosis (DVT) with or without pulmonary embolism (PE), is globally the third most frequent acute cardiovascular syndrome behind myocardial infarction and stroke (1,2).